Breathing patterns and ventilatory efficiency in elderly cardiac patients with and without left ventricular dysfunction before and after exercise-based cardiac rehabilitation: the EU-CaRE study. (3rd October 2022) - Eser, P; Marcin, T; Prescott, E; Prins, L; Kolkmanm, E; Bruins, W; Van Der Welde, A; Pena Gil, C; Illou, M C; Ardission, D; Zeymer, U; Meindersma, E P; et al.
Abstract: Introduction: Coronary artery disease (CAD) may progress to left ventricular dysfunction (LVD) and chronic heart failure. A reduced ventilatory efficiency in these patients is associated with worse outcome. However, breathing patterns at rest and during exercise and their change during exercise-based cardiac rehabilitation (exCR) have been poorly described in this population. We aimed to analyse respiratory and gas-exchange parameters in elderly patients with CAD included in a multicentre study on effectiveness of exCR across seven European countries (EU-CaRE). Methods: Patients aged 65 years and older with acute (ACS) and chronic coronary syndromes (CCS) who participated in exCR were included. Cardiopulmonary exercise testing (CPET) was performed before (T0) and at termination of exCR (T1), and 12 months after start of exCR (T2). Ventilation (VE), breathing frequency (BF), and end-expiratory carbon dioxide pressure (PetCO2) were measured at rest, at first ventilatory threshold and peak exercise. Ventilatory efficiency, expressed as VE/VCO2 slope and the nadir of VE/VCO2 ratio were measured during the ramp test. Peak oxygen uptake was averaged over 30 s. Breathing parameters over time were compared between patients without and with left ventricular dysfunction (LVD, defined as LV ejection fraction <45%) by mixed linear models corrected for age, sex and body mass index. Results: 818 out of 1633 patients of the EU-CaRE study fulfilled inclusion criteria, 151 (18%) had LVD, of these, 86% were in New York Heart Association (NYHA) functional class I. Mean age was 72.5±5.4 years, 21.9% were women, and 79.8% had acute ACS. Compared to patients without LVD, in patients with LVD resting VE was increased 9%, VE/VCO2 slope 14%, and nadir VE/VCO2 ratio 9%, while PetCO2 was reduced at rest and peak exercise by 6%. From before to after exCR, resting ventilation and breathing frequency, as well as VE/VCO2 slope and nadir VE/VCO2 during exercise decreased significantly more in patients with LVD compared to patients without, while improvement in peak oxygen uptake was similar (Figure 1). Conclusions: In contrast to their own perception based on NYHA class, patients with LVD had exaggerated breathing at rest and as response to exercise with consistently reduced PetCO2 and ventilatory efficiency. Abnormal breathing patterns may be an early and clinically relevant sign of LVD and linked to increased chemosensitivity and/or abnormal ergoreflex. Exercise-based CR may contribute to improvements of breathing patterns and ventilator efficiency in this population. Funding Acknowledgement: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): European Union's Horizon 2020 research and innovation program and Swiss State Secretariat for Education, Research and Innovation for the Swiss consortium partner